On the Erd\H{o}s-Ulam problem in the plane : Erd\H{o}s-Ulam problem - Agama, Theophilus (My University, 2023)
In this paper we apply the method of compression to construct a dense set of points in the plane at rational distance from each other. We provide a positive solution to the Erd\H{o}s-Ulam problem
Keywords: admissible points